Examining the oral communication strategies used by a group of Nepalese adult learners in an ESL context - Manzano, Brendalyn Agtarap (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper sought to examine the oral communication strategies (CSs) used by a group of Nepalese adult learners in an oral task in an ESL context. There has been a long history of CS studies in L2 acquisition research; however, there are no studies yet reporting the CSs employed by Nepalese learners in an ESL context. Hence, six Nepalese learners with intermediate language proficiency were engaged in a picture storytelling task. Their narrations were recorded and transcribed, and their responses during the interview were elicited. Four significant results were revealed. Firstly, the Nepalese learners experienced a considerable amount of communication difficulties as manifested by various gap markers. To overcome these problems, the learners simultaneously used a variety of non-verbal CSs alongside verbal CSs. Secondly, linguistic errors were abound in their narrations but were ignored due to their communication goal. Hence, there are areas of communication (e.g., vocabulary and sentence structure) where the learners were having trouble, and these concerns should require instructional attention. Thirdly, the majority of the verbal CSs were avoidance strategies while most of the non-verbal CSs were achievement strategies. Lastly, examining the CSs used by the learners paved the way to culture-based strategies that were employed during storytelling. These CSs provided new inputs to the existing CS frameworks used by English language learners. Implications for language teaching and learning as well as future research are discussed.